Cirrhosis regression after SVR with indirect methods of fibrosis analysis: How far is it real? - Barbosa, Walnei Fernandes [UNESP]; Andrade, Vanessa Gutierrez [UNESP]; Braz, Aline Márcia Marques [UNESP]; Winckler, Fernanda Cristina [UNESP]; Barbosa, Livia Roma; Golim, Marjorie de Assis [UNESP]; Silveira, Liciana Vaz de Arruda [UNESP]; Simões, Rafael Plana [UNESP]; Silva, Giovanni Faria [UNESP] (Springer Nature, 2021)
Hepatitis C virus has infected over 71 million people worldwide, and it is the main cause of cirrhosis in the western world. Currently, the treatment involves direct-acting antiviral agents (DAAs) and its main goal is to achieve sustained virologic response (SVR). The aim of this study was to evaluate the impact of SVR using DAAs in the improvement of liver fibrosis using scores evaluation by indirect method, liver function, and inflammation indirect biomarkers. Patients with cirrhosis with SVR after treatment (n = 104) were evaluated using liver function scores, indirect fibrosis methods, alpha-fetoprotein, and ferritin at t-base and t-SVR. Statistically significant positive results in all parameters were observed: 54 patients were classified as 5 in the CP score in t-base, and 77 in t-SVR; a significant decrease was observed in MELD score, alpha-fetoprotein, ferritin, APRI, FIB-4 and liver stiffness in liver elastography. We did not observe difference in the liver function scores between regressors and non-regressors of liver stiffness, as well as in indirect inflammation biomarkers. The measurements of fibrosis using the indirect methods have significantly decreased in patients with cirrhosis treated who achieved SVR associated with decreased indirect inflammation biomarkers and improved liver function scores.
Keywords: Cirrhosis; DAAs; Fibrosis regression; HCV; Stiffness